The Relevance of the Social Sciences for Legal Education - Tim Berard (Legal Education Review)
Research indicates that the dropout rate for first year students in universities is traditionally higher than for later years, with external or distance students posing the highest risk of withdrawal from studies of any group. This has been the case with the Bachelor of Taxation in the Australian School of Taxation, Faculty of Law at the University of New South Wales. The Bachelor of Taxation (BTax) program is offered nationally in an off-campus delivery mode and focuses on teaching taxation and commercial law as well as economics and accounting. The majority of its students are in full-time employment, are studying part-time and are generally in the late 20s to early 40s age group. Student peer mentoring has been successfully employed in Australia and elsewhere, as a strategy to support first year university students in their studies. In view of this, the Australian School of Taxation (Atax) introduced a peer mentoring program in 2002 aimed at improving the adjustment of first year students to studying at university. The development of this program was part of the ‘First Year Experience Project’ established by the University of New South Wales to improve the quality of the educational experiences and outcomes for first year students. Mentors were selected from continuing Atax students and also included some recent graduates from the program. An existing mentoring program was adapted to suit the demands of distance learning. This article considers the development and analyses the effectiveness of the BTax student peer mentoring program with particular reference to two cohorts of first year students (in 2002 and 2006). It concludes that the majority of the first year students involved in the student peer mentoring program considered that it helped them to adjust to university study. The mentors reinforced the students’ perceptions, agreeing that the program improved the mentees’ learning approaches and adjustment to university. Furthermore, the mentors identified that the program increased their own self-confidence, as well as benefitting their social and communication skills.